DESCRIPTION OF PATIENT SATISFACTION LEVEL OF HEALTH SERVICES IN PUSKESMAS CIBAREGBEG - Ela Mulyana Arofah; Rita Damayanti; Sabarinah Sabarinah (Dian Nuswantoro Semarang, 2022)
Background: Patient satisfaction can be interpreted as the patient's response to the discrepancy between the level of expectations and the actual performance they feel after using the service. Satisfactory and quality service will shape patient loyalty. Purpose: The purpose of this study is to analyze the level of satisfaction and conformity between expectations and reality received by patients with outpatient services in Puskesmas Cibaregbeg based on aspects of service quality dimensions. Methods: The method in this study is quantitative with measurements using a Likert Scale. The sample size in this survey was 380 who received types of services at the Puskesmas Cibaregbeg. Sampling in this survey used cluster random sampling technique. Result: The value of the customer Satisfaction Index is 76.79 % in the interval 76.61–88.30. So that the qualit of service unit performance is